2020
DOI: 10.1515/gps-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Trillium govanianum Wall. Ex. Royle rhizomes extract-medicated silver nanoparticles and their antimicrobial activity

Abstract: Synthesis of nanoparticles is a fast-growing area of interest in the current development in science and technology. Nanoparticles are also used in biomedical applications. Green synthesis of nanoparticles is an environmental friendly and cost-effective technique. Trillium govanianum Wall. Ex. Royle crude extract was used for the eco-friendly genesis of silver nanoparticles (AgNPs). Aromatic amines were the functional groups involved in the bio-fabrication and synthesis of the AgNPs. The production of AgNPs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Compared with the chemical method, the biological method can avoid the use of toxic chemical reducing agents and stable dispersants [21,22]. The raw materials are easy to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the chemical method, the biological method can avoid the use of toxic chemical reducing agents and stable dispersants [21,22]. The raw materials are easy to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…Ex. Royle crude extract, reporting the spherical shape of NPs having a particle size between 6.5 and 65.5 nanometer [76]. Similarly, Sadeghi et al revealed that the size of synthesized stevia leaf extract-based AuNPs was between 21 and 45 nanometer and was spherical in shape [77].…”
Section: Discussionmentioning
confidence: 99%
“…FTIR spectra of plant extract is shown in figure 6(c). The presence of vibrational band within the range of 1300-1700 cm −1 was due to the functional groups of proteins i.e., C=O, −C−N, which resulted in the formation of the amide bands [46]. Similarly, the Alcohols and phenols produce characteristic infrared bands due to O-H stretching and C-O stretching in the regions around 1000 cm −1 , whereas, presence of -NH or moisture causes similar results [47].…”
Section: Optical Analysismentioning
confidence: 90%